Importance of xenarthrans in the eco-epidemiology of Paracoccidioides brasiliensis - Richini-Pereira, Virgínia [UNESP]; Bosco, Sandra [UNESP]; Theodoro, Raquel [UNESP]; Barrozo, Lígia; Pedrini, Silvia; Rosa, Patrícia; Bagagli, Eduardo [UNESP] (Springer Nature, 2009)
Background. Several pathogens that cause important zoonotic diseases have been frequently associated with armadillos and other xenarthrans. This mammal group typically has evolved on the South American continent and many of its extant species are seriously threatened with extinction. Natural infection of armadillos with Paracoccidioides brasiliensis in hyperendemic areas has provided a valuable opportunity for understanding the role of this mammal in the eco-epidemiology of Paracoccidioidomycosis (PCM), one of the most important systemic mycoses in Latin America. Findings. This study aimed to detect P. brasiliensis in different xenarthran species (Dasypus novemcinctus, Cabassous spp., Euphractus sexcinctus, Tamandua tetradactyla and Myrmecophaga tridactyla), by molecular and mycological approaches, in samples obtained by one of the following strategies: i) from road-killed animals (n = 6); ii) from naturally dead animals (n = 8); iii) from animals that died in captivity (n = 9); and iv) from living animals captured from the wild (n = 2). Specific P. brasiliensis DNA was detected in several organs among 7/20 nine-banded armadillos (D. novemcinctus) and in 2/2 anteaters (M. tridactyla). The fungus was also cultured in tissue samples from one of two armadillos captured from the wild. Conclusion. Members of the Xenarthra Order, especially armadillos, have some characteristics, including a weak cellular immune response and low body temperature, which make them suitable models for studying host-pathogen interaction. P. brasiliensis infection in wild animals, from PCM endemic areas, may be more common than initially postulated and reinforces the use of these animals as sentinels for the pathogen in the environment. © 2009 Bagagli et al; licensee BioMed Central Ltd.
Keywords: Animalia; Armadillo; Cabassous; Dasypodidae; Dasypus novemcinctus; Edentata; Euphractus sexcinctus; Fungi; Mammalia; Myrmecophaga tridactyla; Myrmecophagidae; Paracoccidioides brasiliensis; Tamandua tetradactyla; Xenarthra